Answer:
a
Step-by-step explanation:
bc its the only one that makes sence to me heheh
Answer: Option D
Step-by-step explanation:
A relationship is a function if and only if for each input value x (domain) only one output value y is assigned (Range)
Option A.
Note that x represents the input values and y represents the output values.
When [tex]x = 3[/tex] then [tex]y = 14[/tex] and [tex]y = 19[/tex].
The input value [tex]x = 3[/tex] has two output values y assigned.
So the relationship is not a function
Option B.
Note that x represents the input values and y represents the output values.
When [tex]x = 3[/tex] then [tex]y = 0[/tex] and [tex]y = -5[/tex].
The input value [tex]x = 3[/tex] has two output values y assigned.
So the relationship is not a function
Option C
Note that x represents the input values and y represents the output values.
When [tex]x = -1[/tex] then [tex]y = -11[/tex] and [tex]y = 5[/tex].
[tex](-1,-11)[/tex] , [tex](-1, 5)[/tex]
The input value [tex]x = -1[/tex] has two output values y assigned.
So the relationship is not a function
Option D
Note that x represents the input values and y represents the output values and for each input value x (domain) only one output value y is assigned (Range)
[tex]\{(-5, 3), (-3, 1), (-1, -1), (1, -1), (3, 1), (5, 3)\}[/tex]
So the relationship is a function
The average (arithmetic mean) of k scores
is 20. The average of 10 of these scores
is 15. Find the average of the remaining
scores in terms of k.
(A) 20k +150/10
(B) 20k -150/10
(C) 150-20k/10
(D) 150 - 20k/k-10
(E) 20k -150/k-10
Answer:
(E) (20k - 150)/(k - 10)
Step-by-step explanation:
Sum of all scores = average × number of scores = 20 × k = 20k
Sum of 10 scores = 15 × 10 =150
Sum of remaining scores = 20k - 150
Number of remaining scores = k -10
Average of remaining scores = sum of remaining/no. remaining
= (20 k -150)/(k-10)
Alex and Rachel agreed to form a partnership. The partnership agreement requires that Alex
invest $3000 more than two- third of what Rachel is to invest. If the partnerships’ capital is to be
$55,000, how much should Alex invest?
Answer:
Alex investment = $ 23,800
Step-by-step explanation:
The statement is Alex and Rachel are forming partnership. According to the agreement Alex invest $3000 more than Rachel's two-third investment and the total capital is $55,000.Find out Alex investment.
Let x be the investment of Rachel. Lets make an equation to find the value of x.
x+2/3x +$3000=$55,000
Combine the like terms:
x+2/3x = 55,000 - 3000
x+2/3x = $52000
Now take the L.C.M of L.H.S
3x+2x/3 = $52000
Now Add the values of x.
5x/3 = $52000
Multiply both the terms by 3.
5x/3 *3 = 3* $52000
5x= 156000
Now divide both the sides by 5.
5x/5 = 156000/5
x= 31200
Now calculate Alex investment. According to the statement Alex invest $3000 more than 2/3 of Rachel.
We have found the Rachel investment which is $31200. Therefore we can write 2/3 of Rachel investment as 2/3(31200).
=2/3(31200)+$3000
=2*10400+3000
=20,800+3000
=$23,800
Rachel investment = $31200
Alex investment = $ 23,800
If you want to check whether the investments are correctly determined or not. You can add both the investments and the result will be the partnership's capital amount.
$31200+$ 23,800 = $55,000 ....
How can x^2+3x+1=2x^2+2x+3 be set up as a system of equations?
Answer:
System of equations of x^2+3x+1=2x^2+2x+3 is x^2-x+2=0.
Step-by-step explanation:
We need to make system of equations of:
x^2+3x+1=2x^2+2x+3
Solving,
Adding -2x^2 on both sides
x^2+3x+1-2x^2=2x^2+2x+3-2x^2
-x^2+3x+1=2x+3
Adding -2x on both sides
-x^2+3x+1-2x=2x+3-2x
-x^2+x+1=3
Adding -3 on both sides
-x^2+x+1-3=3-3
-x^2+x-2=0
Multiplying with -1
x^2-x+2=0
System of equations of x^2+3x+1=2x^2+2x+3 is x^2-x+2=0.
Men and women (ages 22–40) were surveyed to choose a favorite free-time activity: playing sports, dancing, or watching movies/TV. The survey showed the following frequencies: Men—playing sports: 11; dancing: 3; watching movies/TV: 6 Women—playing sports: 5; dancing: 16; watching movies/TV: 9 Which of the following is a correct two-way frequency table for the data?
can you please add the answers to choose from? I'd like to help
Answer:
B. The second graph displayed.
Step-by-step explanation:
Recieved an 100% on my test with this question!!
Hope I could help! (´⊙◞⊱◟⊙`)
If the figure below is rotated 90degrees clockwise about the origin, what is the new location? the options are:
A’ (0, 8), B’ (6, 0), C’ (0, -8), D’ (0, -6)A’ (-8, 0), B’ (0, 6), C’ (8, 0), D’ (0, -6)A’ (0, 8), B’ (6, 0), C’ (0, -8), D’ (-6, 0)A’ (0, -8), B’ (6, 0), C’ (0, 8), D’ (-6, 0)
Answer:
A'(0, -8), B'(6, 0), C'(0, 8), D'(-6, 0)
Step-by-step explanation:
Whenever you are doing a 90° clockwise rotation ABOUT THE ORIGIN, it is in the form of [y, -x], meaning you take the y and make it your x, then take your original x and put its OPPOSITE.
90° counterclockwise rotation → [-y, x]
90° clockwise rotation → [y, -x]
I hope this helps, and as always, I am joyous to assist anyone at any time.
Please show to answer this
Answer:
[tex](q \circ r)(7)=22[/tex]
[tex](r \circ q)(7)=8[/tex]
Step-by-step explanation:
1st problem:
[tex](q \circ r)(7)=q(r(7))[/tex]
r(7) means to replace x in [tex]\sqrt{x+9}[/tex] with 7.
[tex]r(7)=\sqrt{7+9}=\sqrt{16}=4[/tex]
[tex](q \circ r)(7)=q(r(7))=q(4)[/tex]
q(4) means replace x in [tex]x^2+6[/tex] with 4.
[tex]q(4)=4^2+6=16+6=22[/tex].
Therefore,
[tex](q \circ r)(7)=q(r(7))=q(4)=22[/tex]
2nd problem:
[tex](r \circ q)(7)=r(q(7))[/tex]
q(7) means replace x in [tex]x^2+6[/tex] with 7.
[tex]q(7)=7^2+6=49+6=55[/tex].
So now we have:
[tex](r \circ q)(7)=r(q(7))=r(55)[/tex].
r(55) means to replace x in [tex]\sqrt{x+9}[/tex] with 55.
[tex]r(55)=\sqrt{55+9}=\sqrt{64}=8[/tex]
Therefore,
[tex](r \circ q)(7)=r(q(7))=r(55)=8[/tex].
hey, need some help with this
Step-by-step explanation:
simplify the equation
5-x(2)-3x(4x-7)/(5-x)(3x)
=10-2x-12x²+21x/15x-3x²
=-12x²-23x+10/15x-3x³
the answer is B
yes, Robot is correct but Irum is not
Answer:
simplify the equation first
5-x(2)-3x(4x-7)/(5-x)(3x)
=10-2x-12x²+21x/15x-3x²
=-12x²-23x+10/15x-3x³
the answer is B
Step-by-step explanation:
:)
what is the first term of the sequence below? ___1, 5,25,125
Answer:
The first term of the sequence is 1/5
Step-by-step explanation:
The first term is 1/5.
The reason is that there is a common ratio between each term. In this case multiplying the previous term in the sequence by 5 would give the next term.
So in this case 1/5 is the first term.
If we multiply 1/5 by 5, it will give the next term which is 1.
1/5*5=1
Thus the first term in the sequence = 1/5....
Please answer this correctly
Answer:
Step-by-step explanation:
When you divide by 100, the decimal moves 2 places to the left.
847.8
When you have moved the decimal 3 places to the left, you have divided by 1000
To reverse the effects of 847.8 by dividing by 10000 you need to multiply by 10000
847.8 * 10000 = 8478000 Try this on your calculator to confirm it.
Same with the last one. To get 847.8 when you have divided by 1 million, you movie the decimal in the answer 6 places.
847.8 * 1000000 = 847800000
If f(x) = 2x - 6 and g(x) = 3x + 9, find (f - g)(x).
O A. (f- g)(x) = x+15
O B. (f- g)(x) = -x+3
OC. (f- g)(x) = -x - 15
O D. (f- g)(x) = 5x + 3
[tex](f-g)(x)=2x-6-(3x+9)=2x-6-3x-9=-x-15[/tex]
Answer:
The correct option is C.
Step-by-step explanation:
The correct option is C.
We have given:
f(x) = 2x - 6 and g(x) = 3x + 9
Now we have to find (f-g)(x)
(f-g)(x) = f(x)- g(x)
Now subtract g(x) from f(x)
(2x - 6) - (3x + 9)
Open the parenthesis. When we open the parenthesis the signs of second bracket will become negative because there is a negative sign outside the bracket.
(f-g)(x)= 2x-6-3x-9
Now solve the like terms:
(f-g)(x)= -x-15
Thus the correct option is C....
Which best describes the graph of the cubic function f(x) = x^3 +x^2 +x +1?
A. x increases, y increases along the entire graph.
B. As x increases, y increases, decreases, and then increases again.
C. As x increases, y decreases, increases and then decreases again.
D. As x increases, y decrease along the entire graph.
Answer:
A.
Step-by-step explanation:
Now since the degree is odd (3 in this case) and the leading coefficient is positive (1), then the end behavior is going to be:
for left-end behavior, it is down
for right-end behavior, it is up
We are going to definitely have some increasing action going on because it goes from down to up reading from left to right.
Let's graph it in our ti-84's or whatever you have.
This is a very rough graph but you can see it is just increasing on the entire domain. This means reading the graph from left to right, there is only rise.
I can give you an answer with calculus in it if you prefer.
Question 1 of 10
2 Points
If F(x) = x- 5 and G(x) = x?, what is G(F(x))?
O A. x2(x-5)
O B. x2 + x-5
O C. (X - 5)2
O D. x2.5
SUBMIT
Answer:[tex]\large\boxed{C.\ (x-5)^2}[/tex]Step-by-step explanation:
[tex]f(x)=x-5,\ g(x)=x^2\\\\g\bigg(f(x)\bigg)-\text{put}\ x-5\ \text{expression instead of}\ x\ \text{in}\ g(x):\\\\g\bigg(f(x)\bigg)=(x-5)^2[/tex]
SUBJECT: Algebra
LESSON: Multiplying Polynomials
(x^3 + 2x − 3)(x^4 − 3x^2 + x)
Answer:
Step-by-step explanation:
(x^3 + 2x − 3)(x^4 − 3x^2 + x)
Multiply each value of 2nd bracket with 1st bracket:
=x^4(x^3 + 2x − 3) - 3x^2(x^3 + 2x − 3) +x(x^3 + 2x − 3)
=x^7+2x^5-3x^4-3x^5-6x^3+9x^2+x^4+2x^2-3x
Now combine the terms with same power:
=x^7-x^5-2x^4-6x^3+11x^2-3x
You can also take the common from the expression:
x(x^6-x^4-2x^3-6x^2+11x-3)....
The product of (x^3 + 2x − 3)(x^4 − 3x^2 + x) is x(x^6-x^4-2x^3-6x^2+11x-3)....
Kinley bought 3 notebooks that cost the same and a poster that cost $6. She spent $20.40 in all. What was the cost of each notebook?
Answer:
the cost of each notebook is $4.8
Step-by-step explanation:
Cost of each notebook= ?
Cost of a poster = $6
Total amount she spent = $20.40
If we subtract the cost of poster from total amount we get the cost of 3 notebooks.
$20.40-$6
=$ 14.4
It means the cost of 3 notebooks = $14.4
To find the cost of each notebook divide the cost of 3 notebooks by the number of books.
=14.4/3
=$4.8
Thus the cost of each notebook is $4.8....
Find the exact value of sec30º.
Answer:
2 /√3 or 2√3 / 3.
Step-by-step explanation:
Referring to the 30-60-90 triangle: hypotenuse = 2 , smaller leg = 1 and longer leg = √3 and the shorter side is opposite the 30 degree angle.
So cos 30 = √3/2
Sec 30 = 1 / cos 30
= 2 /√3
or 2√3 / 3.
The exact value of sec(30º) using trigonometric identity for secant is 2.
To find the exact value of sec(30º), use the trigonometric identity for secant:
sec(θ) = 1/cos(θ)
Using the special right triangle with angles 30º, 60º, and 90º, it is known that the side lengths are in the ratio 1:√3:2.
The cosine is defined as the adjacent side divided by the hypotenuse.
For a 30º angle, the adjacent side = 1 and the hypotenuse = 2.
So, cos(30º) = 1/2
Substituting this into the formula for secant:
sec(30º) = 1/cos(30º)
= 1/(1/2)
= 2
Therefore, the exact value of sec(30º) is 2.
Learn more about Trigonometry here:
https://brainly.com/question/12068045
#SPJ6
PLEASE HELP!!!!!!!!!!!!!!Given that B, C, and D are the midpoints of AZYA, find the perimeter of AZYA.
A. 70.6
B. 72.6
C. 76.6
77.6
Factor the given expression.
x2 + 16
+ 64
O A. (x+4)2
B. (x + 16)(x + 4)
c. (x+3)(x - 8)
OD. (x+8)2
Answer:
D. (x+8)^2
Step-by-step explanation:
x^2 + 16x + 64
We are factoring a quadratic trinomial in which the first term is x^2.
We need to find two numbers whose product is 64 and whose sum is 8.
8 * 8 = 64
8 + 8 = 16
The numbers are 8 and 8.
x^2 + 16x + 64 = (x + 8)(x + 8) = (x + 8)^2
Check: If (x + 8)^2 is indeed the correct factorization of x^2 + 16x + 64, then if you multiply out (x + 8)^2, you must get x^2 + 16x + 64.
(x + 8)^2 =
= (x + 8)(x + 8)
= x^2 + 8x + 64
= x^2 + 16x + 64
We get the correct product, so our factorization is correct.
Suppose that g(x) = f(x) - 3. Which statement best compares the graph of
g(x) with the graph of Rx)?
Answer:
The graph of g(x) is a translation of f(x) 3 units down.
Step-by-step explanation:
The given function is
[tex]g(x) = f(x) - 3[/tex]
The parent function now is f(x).
The -3 tells us that there is a vertical translation of the parent function 3 units down.
Therefore the graph of g(x) is obtained by translating the graph of f(x) down by 3 units.
Find the value of x in the picture please
Answer:
The value of x is 4
Step-by-step explanation:
we know taht
The intersecting chords theorem states that the products of the lengths of the line segments on each chord are equal.
so
In this problem
[tex](12)(x)=(8)(x+2)[/tex]
solve for x
[tex]12x=8x+16[/tex]
[tex]12x-8x=16[/tex]
[tex]4x=16[/tex]
[tex]x=4[/tex]
the inverse of f(x)=4x+5
To find the inverse of a function switch the place of y (aka f(x) ) with x. Then solve for y.
Original equation:
y = 4x + 5
Switched:
x = 4y + 5
Solve for y by isolating it:
x - 5 = 4y + 5 - 5
x - 5 = 4y
(x - 5)/4 = 4y/4
[tex]\frac{1}{4}x-\frac{5}{4} = y[/tex]
Hope this helped!
~Just a girl in love with Shawn Mendes
Mr. Gomez owns a carpet cleaning bus
different jobs his company was hired to do. For
carpet cleaning business. Problems 1-4 show four
pany was hired to do. For each situation:
Let a represent the initial charge (1
the house.
present the initial charge in dollars) for coming to
Let b represent the number of hours the job takes.
Let c represent the charge (in dollars) for each hour the
job takes.
Let d represent the total cost in dollars) of the job.
1. Determine the total cost of a job.
a. If a = 60, b = 4, and c = 50, write an equation for calculating the total
Answer:
a) The equation of the total cost is d = a + bc
The equation for calculating the total is d = 60 + 4(50)
b) The total cost for the job is $260
Step-by-step explanation:
* Lets explain how to solve the problem
- Mr. Gomez owns a carpet cleaning business
- The situation of the job;
# a represents the initial charge (in dollar) for coming to the house
# b represents the number of hours the job takes
# c represents the charge (in dollars) for each hour the job takes
# d represents the total cost (in dollars) of the job
* Lets make the equation of the total cost
∵ The initial amount of the job is a dollars
∵ The number of hours the job takes is b
∵ The charge per hour is c dollars
∵ The total cost of the job is d
- The total cost is the sum of the initial amount and the product of
the number of hours the job takes and the charge per hour
∵ The total cost = initial amount + the number of hours × charge
per hour
∴ d = a + b × c
∴ d = a + bc
a)
* The equation of the total cost is d = a + bc
∵ a = $60 , b = 4 hours , c = $50
∴ d = 60 + 4(50)
* The equation for calculating the total is d = 60 + 4(50)
b)
∵ d = 60 + 4(50)
∴ d = 60 + 200
∴ d = 260
* The total cost for the job is $260
use a graphing calculator to solve the equation 3tan1/3theta=8 in the interval 0 to 2pi round your answers to the nearest hundredth
A. 1.21,4.35
B. 3.64
C. 1.21, 2.26, 3.31, 4.35, 5.40
D. .404, 1452.5, 3.55, 4.59, 5.64
Answer:
B. 3.64 to the nearest hundredth.
Step-by-step explanation:
3tan1/3theta=8
tan1/3theta = 8/3
1/3 theta = 1.212 radians, 1.212 + π radians.
theta = 1.212 * 3 = 3.636 radians, 3(1.212 + π) radians.
The second value is greater than 2π radians.
The correct answer is C. 1.21, 2.26, 3.31, 4.35, 5.40.
To solve the equation [tex]\( 3 \tan \frac{1}{3}\theta = 8 \)[/tex] in the interval[tex]\( 0 \) to \( 2\pi \)[/tex], we first isolate [tex]\( \tan \frac{1}{3}\theta \):[/tex]
[tex]\[ \tan \frac{1}{3}\theta = \frac{8}{3} \][/tex]
Next, we take the inverse tangent (arctan) of both sides to solve for
[tex]\[ \frac{1}{3}\theta = \arctan\left(\frac{8}{3}\right) \][/tex]
Now, we multiply both sides by 3 to solve for [tex]\( \theta \)[/tex]:
[tex]\[ \theta = 3 \cdot \arctan\left(\frac{8}{3}\right) \][/tex]
Using a graphing calculator, we find the values of [tex]\( \theta \)[/tex] that satisfy the equation within the interval [tex]\( 0 \)[/tex] to[tex]\( 2\pi \)[/tex]. The calculator will give us the principal value and we need to consider all solutions within the given interval, taking into account the periodicity of the tangent function.
The principal value for [tex]\( \arctan\left(\frac{8}{3}\right) \)[/tex] is approximately[tex]\( 1.21 \)[/tex] radians. Since the tangent function has a period of[tex]\( \pi \)[/tex], we add multiples of[tex]\( \pi \)[/tex] to find other solutions within the interval [tex]\( 0 \)[/tex] to [tex]\( 2\pi \).[/tex]
[tex]\[ \theta \approx 1.21 + k\pi \][/tex]
where [tex]\( k \)[/tex] is an integer such that[tex]\( \theta \)[/tex] remains within the interval [tex]\( 0 \)[/tex] to[tex]\( 2\pi \).[/tex]
For[tex]\( k = 0 \):[/tex]
[tex]\[ \theta \approx 1.21 \][/tex]
For [tex]\( k = 1 \):[/tex]
[tex]\[ \theta \approx 1.21 + \pi \approx 4.35 \][/tex]
For[tex]\( k = 2 \):[/tex]
[tex]\[ \theta \approx 1.21 + 2\pi \approx 7.49 \][/tex]
However, this value is outside our interval, so we do not include it.
For[tex]\( k = 3 \):[/tex]
[tex]\[ \theta \approx 1.21 + 3\pi \approx 10.63 \[/tex]]
This value is also outside our interval, so we do not include it.
Since the tangent function is periodic with a period of [tex]\( \pi \),[/tex] we also need to consider the solutions in the second half of the interval[tex]\( 0 \)[/tex] to [tex]\( 2\pi \),[/tex] which are obtained by subtracting the principal value from[tex]\( 2\pi \):[/tex]
[tex]\[ \theta \approx 2\pi - 1.21 + k\pi \][/tex]
[tex]\[ \theta \approx 2\pi - 1.21 + k\pi \][/tex]
For [tex]\( k = 0 \)[/tex]:
[tex]\[ \theta \approx 2\pi - 1.21 \approx 5.40 \][/tex]
For [tex]\( k = 1 \)[/tex]:
[tex]\[ \theta \approx 2\pi - 1.21 + \pi \approx 8.54 \][/tex]
This value is outside our interval, so we do not include it.
Therefore, the solutions within the interval[tex]\( 0 \)[/tex] to [tex]\( 2\pi \)[/tex], rounded to the nearest hundredth, are: [tex]\[ \boxed{1.21, 2.26, 3.31, 4.35, 5.40} \][/tex]
Note that [tex]\( 2.26 \)[/tex] and [tex]\( 3.31 \)[/tex] are obtained by adding [tex]\( \pi \) to \( 1.21 \)[/tex] and [tex]\( 2.26 \)[/tex]respectively, which are the first two solutions in the first half of the interval. These values are within the interval [tex]\( 0 \) to \( 2\pi \)[/tex] and are also solutions to the original equation.
Write the Explicit Rule for the arithmetic sequence:
an = a1 + (n-1)d
1, 3, 5.7. ...
[tex]a_1=1\\d=2\\a_n=1+(n-1)\cdot 2=1+2n-2=2n-1[/tex]
How do you graph
f(x)=7sec(2x)
Answer:
We know that sec(x) = 1/cos(x). Therefore:
7sec(2x) = 7/cos(2x).
The function won't be define at the points where the denomitator equals zero, which is when x=(2n+1)π/2.
Using a graphing calculator, we get that the graph of the function is the one attached.
simplify 3 divided by 5-6i
Answer:
[tex]\frac{15}{61}+\frac{18}{61}i[/tex]
Step-by-step explanation:
[tex]\frac{3}{5-6i}[/tex]
To simplify or to write in the form a+bi, you will need multiply the top and bottom by the bottom's conjugate like so:
[tex]\frac{3}{5-6i} \cdot \frac{5+6i}{5+6i}[/tex]
Keep in mind when multiplying conjugates you only have to multiply first and last.
That is the product of (a+b) and (a-b) is (a+b)(a-b)=a^2-b^2.
(a+b) and (a-b) are conjugates
Let's multiply now:
[tex]\frac{3}{5-6i} \cdot \frac{5+6i}{5+6i}=\frac{3(5+6i)}{25-36i^2}[/tex]
i^2=-1
[tex]\frac{15+18i}{25-36(-1)}[/tex]
[tex]\frac{15+18i}{25+36}[/tex]
[tex]\frac{15+18i}{61}[/tex]
[tex]\frac{15}{61}+\frac{18}{61}i[/tex]
For this case we must simplify the following expression:
[tex]\frac {3} {5-6i}[/tex]
We multiply by:
[tex]\frac {5 + 6i} {5 + 6i}\\\frac {3} {5-6i} * \frac {5 + 6i} {5 + 6i} =\\\frac {3 (5 + 6i)} {(5-6i) (5 + 6i)} =\\\frac {3 (5 + 6i)} {5 * 5 + 5 * 6i-6i * 5- (6i) ^ 2} =\\\frac {3 (5 + 6i)} {25-36i ^ 2} =\\\frac {3 (5 + 6i)} {25-36 (-1)} =\\\frac {3 (5 + 6i)} {25 + 36} =\\\frac {3 (5 + 6i)} {61} =\\\frac {15 + 18i} {61}[/tex]
Answer:
[tex]\frac {15 + 18i} {61}[/tex]
#20-12: Simplify this complex fraction. 1/4 / 2/5
Answer:
=1/40
Step-by-step explanation:
=1/8/5
=1/40
What are the center and radius of the circle defined by the equation x^2+y^2-6x+4y+4=0
Answer:
Option B
center (3,2)
radius 3
Step-by-step explanation:
Given:
x^2+y^2-6x+4y+4=0
x^2+y^2-6x+4y=-4
Now completing square of x^2-6x by introducing +9 on both sides:
x^2-6x+9+y^2+4y=-4+9
(x-3)^2+y^2+4y=5
Now completing square of y^2+4y by introducing +4 on both sides:
(x-3)^2+y^2+4y+4=5+4
(x-3)^2 + (y-2)^2= 9
Now comparing with the circle equation:
(x-h)^2 + (y-k)^2= r^2
where
r= radius of circle
h= x-offset from origin
k= y-offset from origin
In given case
r=3
h=3
k=2
Hence, option B is correct with radius =3 and center =(3,2)!
Answer:
Center (3,-2); radius 3
I’m giving all the points I have, plz help and get it right? Someone please help me
Answer:
The area (probability) is: 0.6864.
Step-by-step explanation:
According to the statement, we are in front of a normal distribution with the following parameters:
µ (mean) = 0
σ (Standard deviation) = 1.
Then we need to find the area of the shaded region, which is the area between the points -1.21 < z < 0.84.
And the area (probability) is: 0.6864.
Answer:
A. 0.6864
Step-by-step explanation:
The area of the shaded region between the two z-scores indicated in the diagram is 0.6864.
mean = 0
Standard deviation = 1
What is the final step in solving the inequality -2(5 - 4x)
6x – 4?
Step 1 -10 + 8x < 6x-4
Step 2: -10 <-2x - 4
Step 3: -6<-2x
Step 4
O X<-3
0 x>-3
0 x<3
© x>3
VAVA
Answer:
Answer is x>3
Step-by-step explanation:
The last step is: divide -2 to both sides and since the 2 is negative the sign flips so it would be x>3.
Hope my answer has helped you and if not i'm sorry.
Choose the expression that represents a cubic expression.
a. 19x^4 + 18x^3 - 16x^2 - 12x + 1
b. 10x^3 - 6x^2 - 9x + 12
c. -9x^2 - 3x + 4
d. 4x + 3
Answer:
b. 10x^3 - 6x^2 - 9x + 12
Step-by-step explanation:
A cubic expression has the highest power of the variable to the third power
x^3
b. 10x^3 - 6x^2 - 9x + 12
is the only expression that has the highest power as x^3
a has x^4 and c and d do not have an x^3 term
Final answer:
The expression that represents a cubic expression is (b) [tex]10x^3 - 6x^2 - 9x + 12[/tex], as it is the only option where the highest power of x is three.
Explanation:
The expression that represents a cubic expression is option (b) [tex]10x^3 - 6x^2 - 9x + 12[/tex]. A cubic expression is one in which the highest degree of any term is three, which means the variable (most commonly x) is raised to the third power. Looking at the options provided:
(a) [tex]19x^4 + 18x^3 - 16x^2 - 12x + 1[/tex] is not a cubic expression because it contains a term with x to the fourth power.
(b) [tex]10x^3 - 6x^2 - 9x + 12[/tex] is a cubic expression because the highest power of x is three.
(c)[tex]-9x^2 - 3x + 4[/tex] is not a cubic expression; it's a quadratic expression since the highest power of x is two.
(d) 4x + 3 is also not a cubic expression; it's linear as the highest power of x is one.